Ischemická choroba dolních koncetin a diabetes - Malý, R; Chovanec, V (Vnitrni lekarstvi, 2010)
Peripheral arterial disease (PAD) is a disease characterised by narrowing and blockade of peripheral arteries, usually based on underlying obliterating atherosclerosis. According to the results of large epidemiological studies, the risk of PAD in patients with diabetes mellitus (DM) is fourfold higher compared to non-diabetic population. Patients with DM and PAD have a high risk of cardiovascular morbidity and mortality. Diabetes worsens the prognosis of patients with PAD; the onset of PAD in diabetics occurs at an earlier age, the course is faster than in non-diabetic patients and the disease is often diagnosed at its advanced stages. All these factors reduce the likelihood of revascularisation in DM patients with PAD. A range of factors (higher age, arterial hypertension, smoking, obesity, hyperfibrinogenaemia, insulin resistance etc.) contribute to the development of PAD in DM. Diabetes control is an independent risk factor of PAD as every 1% increase of hemoglobin A1C is associated with 28% increase of PAD. There are different clinical signs of PAD in diabetic and non-diabetic patients. In addition to the history of claudications, PAD diagnostic criteria include the presence of murmur over the large arteries, signs of chronic ischemia on the skin and distal ulcerations and gangrene. Among the imaging techniques, non-invasive investigations including Doppler pressure measurement, ankle brachial pressure index, color duplex ultrasonography, plethysmography, transcutaneous tension measurement, MR and CT angiography are preferred. Ankle brachial pressure index measurement is the easiest and the main investigation technique. The key principles of PAD treatment in diabetic patients include modification of risk factors, pharmacotherapy and revascularisation interventions aimed at improving clinical signs and prevention of cardiovascular morbidity and mortality. Antiplatelet treatment may prevent PAD progression and reduce cardiovascular events in DM patients. Early diagnosis of PAD in DM patients, rigorous prevention and aggressive management of the risk factors may significantly impact on the high incidence of amputations and decrease cardiovascular morbidity and mortality.
Keywords: Humans; Peripheral Vascular Diseases; onemocnění periferních cév; lidé; Diabetic Angiopathies; diabetické angiopatie